Cerebral and Splanchnic Tissue Oxygenation Are Significantly Affected in Premature infants with Ductal-Dependent Congenital Heart Disease - Anastasiya Mankouski, MD; Timothy M. Bahr, MD; Katherine L. Braski, MD; Kimberlee Weaver Lewis, RN; Mariana C. Baserga, MD (Journal of Pediatrics: Clinical Practice)
Objective: To determine whether premature infants with prostaglandin (PGE)-dependent congenital heart disease (CHD) have impaired cerebral and splanchnic oxygenation (rSO2) using near infrared spectroscopy (NIRS). Study design: Cerebral and splanchnic rSO2 were monitored using NIRS for 48 hours in premature infants <36 weeks gestational age with PGE-dependent CHD and control infants (no CHD or patent ductus arteriosus). Both groups were receiving gavage enteral feedings and were >14 days of life. Mixed effects model estimated the effect of CHD and feedings on splanchnic and cerebral NIRS and accounted for multiple measurements on the same participant at 3 different times around feedings (30 minutes before, during, and 30 minutes after feedings). Results: Twenty-four participants were enrolled in the study (10 with CHD and 14 controls). The final dataset included 897 measurements from 23 participants. The median gestational age and birthweight were comparable between case and control groups (34 vs 33 weeks gestational age; mean birthweight of 1811 g vs 1820 g, respectively). On average, cerebral NIRS measurements were 9.5 points higher in controls than cases (P = .003); and splanchnic NIRS measurements were 13.1 points higher in controls than cases (P = .001). The mean cerebral NIRS measurements at baseline, during feeding, and after feeding were 64.0 ± 10.4, 64.5 ± 9.9, and 64.2 ± 9.9 in cases, respectively; and 73.3 ± 6.9, 73.1 ± 6.8, 73.5 ± 6.9 in controls, respectively. The mean splanchnic NIRS measurements at baseline, during feeding, and after feeding were 34.4 ± 15.8, 37.2 ± 14.8, and 38.3 ± 16.1 in cases, respectively; and 50.7 ± 11.0, 51.6 ± 11.1, 50.6 ± 13.5 in controls, respectively. Conclusions: These results demonstrate significantly lower cerebral and splanchnic rSO2 in premature infants with PGE-dependent CHD compared with control infants. These data raise concerns regarding how unrepaired cyanotic CHD can limit systemic oxygenated blood flow chronically, directly contributing to cerebral and gastrointestinal hypoperfusion and ischemia, ultimately increasing the risk for poor neurodevelopmental outcomes and necrotizing enterocolitis in these premature infants.